Mechanism of angiotensin converting enzyme (ACE) inhibition by Syzygium polyanthum wight (WALP.) leaves - Tuan Anuar, Tuan Ashraf Faiz; Ismail, Azlini; Mohamed Suffian, Izzat Fahimuddin; Abdul Hamid, Azzmer Azzar; Omar, Muhammad Nor; Mustafa Al-Ahmad, Basma Ezzat; Wan Ahmad, Wan Amir Nizam (2021)
Syzygium polyanthum is an ethnomedicinal plant used for the treatment of hypertension. This study investigates its antihypertensive property using angiotensin-converting enzyme (ACE) enzyme inhibition assay. This study aims to determine the ACE inhibitory activity of S. polyanthum leaves aqueous extract (ASP), its inhibition specificity and mechanism and the possible bioactive compound. ACE inhibition activity of ASP (1-1000 µg/ml) was tested and compared with standard drug, captopril (2.06 ng/ml). The inhibition mechanism was tested using zinc chloride and bovine serum albumin (BSA). The phytochemical composition in ASP was analyzed using Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry. In silico docking analysis was then performed between the major identified compounds in ASP with ACE. ASP at 100 μg/ml exhibited the highest inhibition activity (69.43 ± 0.60%) compared to MSP (41.63 ± 0.15%), EASP (9.62 ± 1.60%) and also HSP (45.40 ± 0.15%). From the dose-response curve for ACE inhibition activity of ASP, the inhibitory concentration of ASP that causes 50% of ACE inhibition activity (IC50) was 41 μg/ml. ACE inhibition activity by ASP was significantly reduced by the presence of BSA, indicative of interaction of ASP with albumin. ACE inhibition activity by ASP was not significantly affected with the presence of zinc chloride, indicating that its inhibitory activity on ACE was non-dependent of zinc at the ACE active site. There were 26 compounds identified in ASP with 1-galloyl-glucose identified as the major compound. Molecular docking analysis showed that 1-galloyl-glucose has lower binding energy (-7.7 kcal/mol) with ACE, as compared to standard drug, captopril (-5.6 kcal/mol); indicative of good interaction between 1-galloyl-glucose and ACE. In conclusion, this study showed that ACE inhibition activity by S. polyanthum leaves possibly occurs via protein precipitation and was non-dependent to the chelation with zinc at ACE active site, with 1-galloyl-glucose suggested as the potential bioactive compound.